Running out of time - Levy, Elizabeth; Mars, W. T. (New York : Knopf : distributed by Random House, 1980)
While running in the fog early one morning, three friends suddenly find themselves in the Roman Empire of 73 B.C. where they become catalysts in a slave revolt led by the gladiator Spartacus.
Keywords: Slavery -- Fiction; Gladiators -- Fiction; Space and time -- Fiction